Montreal Cognitive Assessment and Mini‐Mental State Examination reliable change indices in healthy older adults. (29th June 2016) - Kopecek, Miloslav; Bezdicek, Ondrej; Sulc, Zdenek; Lukavsky, Jiri; Stepankova, Hana
Abstract : Objective: Cognitive tests are used repeatedly to assess the treatment response or progression of cognitive disorders. The Montreal Cognitive Assessment (MoCA) is a valid screening test for mild cognitive impairment. The aim of our study was to establish 90% reliable change indices (RCI) for the MoCA together with the Mini‐Mental State Examination (MMSE) in cognitively healthy older adults. Method: We analyzed 197 cognitively healthy and functional independent volunteers aged 60–94 years, who met strict inclusion criteria for four consecutive years. The RCI methods by Chelune and Hsu were used. Results: For 1, 2, and 3 years, the 90% RCI for MoCA using Chelune's formula were −4 ≤, ≥4; −4 ≤, ≥4 and −5 ≤, ≥4 points, respectively, and −3 ≤, ≥3 for the MMSE each year. Ninety percent RCI for MoCA using Hsu's formula ranged from −6 to 0, respectively, and +3 to +8 dependent on the baseline MoCA. Conclusion: Our study demonstrated RCI for the MoCA and MMSE in a 3‐year time period that can be used for the estimation of cognitive decline or improvement in clinical settings. Copyright © 2016 John Wiley & Sons, Ltd.